The number of Leydig cells in highfat diet-fed rats after administration of kepok banana peel extract - Zulkifli, Baidillah; Akmal, Muslim; Wahyuni, Sri; Gholib, Gholib; Adam, Mulyadi; Zainuddin, Zainuddin; Lubis, Triva Murtina; Usrina, Nora; Nirmala, Fadya (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
The impact of free radicals on testicular Leydig cells can result in the disruption of male reproductive health. The present study aimed to evaluate the effects of a high-fat diet on Leydig cells and the potential of kepok banana peel extract as a medication to mitigate these effects. In total of 20 adult male Wistar rats were assigned to five groups and treated with standard feed (P1), high-fat feed (P2), high-fat feed with simvastatin (P3), and high-fat feed with banana peel extract at doses of 100 and 200 mg/kg BW (P4 and P5). After 60 days of treatment, the number of Leydig cells was determined using HE staining methods. Data were analyzed using an One Way ANOVA test. The results showed that the administration of 100 mg/kg BW of kepok banana peel extract (P4) was able to maintain the number of Leydig cells and counteract the negative effects of a high-fat diet. These findings suggest that kepok banana peel extract may have the potential as a herbal medicine for supporting male reproductive health.